2017
DOI: 10.1002/stem.2618
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Inducible Factor-1α Potentiates Jagged 1-Mediated Angiogenesis by Mesenchymal Stem Cell-Derived Exosomes

Abstract: Insufficient vessel growth associated with ischemia remains an unresolved issue in vascular medicine. Mesenchymal stem cells (MSCs) have been shown to promote angiogenesis via a mechanism that is potentiated by hypoxia. Overexpression of hypoxia inducible factor (HIF)-1α in MSCs improves their therapeutic potential by inducing angiogenesis in transplanted tissues. Here, we studied the contribution of exosomes released by HIF-1α-overexpressing donor MSCs (HIF-MSC) to angiogenesis by endothelial cells. Exosome s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
238
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 297 publications
(259 citation statements)
references
References 66 publications
(98 reference statements)
5
238
0
1
Order By: Relevance
“…Subcutaneous implantation of Matrigel containing HIF‐MSC‐derived exosomes (enriched in Jagged 1) indicated a significantly higher angiogenesis rate than those derived from control MSCs. As a conclusion, it was demonstrated that hypoxia can increase angiogenic capacity of MSCs through increased packaging of Jagged1 in their exosomes, and suggested as a potential treatment strategy for ischemia‐related diseases …”
Section: Exosomes In Hypoxia Conditionsmentioning
confidence: 88%
“…Subcutaneous implantation of Matrigel containing HIF‐MSC‐derived exosomes (enriched in Jagged 1) indicated a significantly higher angiogenesis rate than those derived from control MSCs. As a conclusion, it was demonstrated that hypoxia can increase angiogenic capacity of MSCs through increased packaging of Jagged1 in their exosomes, and suggested as a potential treatment strategy for ischemia‐related diseases …”
Section: Exosomes In Hypoxia Conditionsmentioning
confidence: 88%
“…Apart from activation of particular genes, overexpression of certain genes that are already present in MSCs also provides some benefits. For example, the hypoxia inducible factor-1α (HIF-1α) has been shown to have angiogenic functions and is present in MSCs [9]. Upon the overexpression of HIF-1α, Jagged1 was found to be more abundant in exosomes derived from the same MSCs, leading them to be pro-angiogenic as well.…”
Section: Msc-derived Exosomesmentioning
confidence: 99%
“…Enhanced microvessel density and blood perfusion in ischemic tissues have been confirmed after exosomes treatment [67]. For example, Gonzalez et al showed that exosomes stably overexpressing hypoxia inducible factor-1α (HIF-1α) exhibit increased angiogenic capacity, in part through an increase in the packaging of Jagged1 [68]. This HIF-1α-based mechanism regulates MSCs-derived exosomes and exosomes-mediated angiogenesis [67].…”
Section: Functional Contribution Of Exosomes In Fibrosis and Angiogenmentioning
confidence: 98%